Susceptibility of Legionella pneumophila Isolated from Air Conditioners to Various Types of Antibiotics in Khartoum State, Sudan - M. A, Elsanousi R.; S.M, El Sanousi (Journal of Veterinary Medicine and Animal Production, 2021)
The aim of this study was to evaluate the susceptibility of Legionella pneumophila isolates obtained from water samples of evaporative coolers conditioners in Khartoum State to various types of antibiotics. The number of isolated Legionella was 222 (42.3%) from a total of 525 samples. The samples were analyzed by conventional methods as well as a Real Time-PCR. Twenty isolates were subjected to disc diffusion test method. Legionella pneumophila isolates were found to be susceptible to the following antibiotics: ciprofloxacin (100%), azithromycin (85%), erythromycin (65%) and tetracycline (50%). Legionella pneumophila was resistant to Amoxicillin / clavulanic acid. Cephalexin, cefotaxim and vancomycin showed only15% sensitivity. From this study it could be concluded that Legionella pneumophila was more susceptible to ciprofloxacin followed by azithromycin than the other tested antibiotics.